SEMIOTIC ANALYSIS DEPICTED IN NBA TEAM LOGOS - Stefanus, Juan; Fadilah, Eka; Kurniawan, Yulius (Universitas Widya Kartika Surabaya, 2023)
The goal of this study was to examine a number of animal-themed NBA team logos. The goal of this study is to decipher the significance behind the NBA team's animal logos. Charles Sander Peirce's semiotic theory, which is broken down into icons, indexes, and symbols, is the theory that the writer employs. The descriptive qualitative methodology is used in this study. Data was gathered from Google by checking up NBA team logos, searching for them, and then choosing the ones that exclusively have animal logos. According to the findings of this study, each animal logo utilized in the NBA team logos has a certain significance based on the traits of each team. The writer also discovered that the background colors of each NBA team logo have significance and are connected to the logos of the NBA teams that employ animal logos. Overall, there is a relationship between the animal depictions and the colors used in each NBA team's logo and the traits of each NBA team, such as identifying toughness, strength, courage, cohesion, agility, attack, defense, and tactics with the primary objective of defeating its opponent.